Electrochemical study of nickel(salen) and cobalt(salen) derivatives complexes in the presence of unsaturated halides - Duñach, E. (2003)
The electrochemical intramolecular cyclisation of allyl 2-bromophenyl ethers in N,N'-dimethylformamide at constant current in a diaphragmless cell has been developed using Ni(II) and Co(II) complexes as electron-transfer mediators. Cyclic compounds are obtained in good yields under appropriate experimental conditions.